DTRMWXHS‐12, a novel Bruton tyrosine kinase inhibitor, in combination with everolimus and pomalidomide in patients with relapsed/refractory lymphomas: An open‐label, multicenter, phase 1a/1b study. Issue 5 (7th March 2023) - Huntington, Scott F.; Schuster, Stephen J.; Ding, Wei; Koehler, Amber B.; Brander, Danielle M.; Rosenthal, Allison C.; Leis, Jose F.; Tun, Han W.; Moustafa, Muhamad Alhaj; Iqbal, Madiha; He, Wei; Kearney, Albert S.; et al.
Abstract: Preclinical studies have shown augmented activity when combining Bruton tyrosine kinase inhibitors (BTKi) with inhibitors of mammalian target of rapamycin (mTOR) and immunomodulatory agents (IMiD). We conducted a phase 1, open‐label study at five centers in USA to evaluate the safety of triplet BTKi/mTOR/IMiD therapy. Eligible patients were adults aged 18 years or older with relapsed/refractory CLL, B cell NHL, or Hodgkin lymphoma. Our dose escalation study used an accelerated titration design and moved sequentially from single agent BTKi (DTRMWXHS‐12), doublet (DTRMWXHS‐12 + everolimus), and then to triplet therapy (DTRMWXHS‐12 + everolimus + pomalidomide). All drugs were dosed once daily on days 1–21 of each 28‐day cycle. The primary goal was to establish the recommended phase 2 dose of the triplet combination. Between September 27, 2016, and July 24, 2019, a total of 32 patients with a median age of 70 years (range 46 to 94 years) were enrolled. No MTD was identified for monotherapy and the doublet combination. The MTD for the triplet combination was determined to be DTRMWXHS‐12 200 mg + everolimus 5 mg + pomalidomide 2 mg. Responses across all studied cohorts were seen in 13 of 32 (41.9%). Combining DTRMWXHS‐12 with everolimus and pomalidomide is tolerable and shows clinical activity. Additional trials could confirm benefit of this all‐oral combination therapy for relapsed/refractory lymphomas.